Financial Toxicity and Strain among Veteran and Civilian Men with Prostate Cancer - Sumlin, Adam B.; Houjaij, Ali; Darwish, Oussama M.; Camacho, Susan; Groman, Adrienne; Fayazi, Zahra (Archives of Clinical and Biomedical Research, 2023)
Purpose: The goal of this study was to examine financial toxicity and strain among Veterans and civilians in two different healthcare facilities. This study was based for the concerns for the rising cost of cancer care which can lead to societal financial toxicity. Societal financial toxicity is discussed at many levels of healthcare policy. Method: A questionnaire was administered to 115 participants (11 Veterans and 104 civilians) for Veteran and civilian men who have been diagnosed with prostate cancer and who may have experienced financial difficulty with treatment or diagnosis. Descriptive statistical analyses (as appropriate: n, percent, mean, median, min and max) will be used to summarize participant characteristics. Factors influencing survival such as PCa diagnosis, treatment, financial toxicity, and Quality of Life (QoL) measures will be examined using a logistic regression model. Results: Men will sustain financial burdens from treatment of prostate cancer, medications, and side effects. Men who have less socioeconomic reserves and poorer ability to interact with the American healthcare system will suffer unreasonably. These men are more likely to be African Americans or Veterans. Therefore, locating the extent of financial burden and developing new interventions to alleviate financial toxicity and thereby financial stress will impact men with socioeconomic disadvantages and reduce disparity. Conclusion: There is a difference among healthcare systems that translate to later diagnosis and more treatments with the outcome not being as favorable to some. Greater cost and intensity of treatment can translate into a greater financial burden and strain, which will impact those with less insurance, financial reserves, and Veteran men specifically who suffer from PCa.